Youth Experience With Community Pharmacy Services and Their Perceptions Toward Implementation of Medication Therapy Management Services by Community Pharmacists in the Western Region of Saudi Arabia. (January 2019) - Alhaddad, Mahmoud S.
Background: Pharmacists are the part of the health care team who can counsel patients on the most appropriate use of medications. This study aims to measure patients' experience with services provided by community pharmacists and their perceptions toward providing medication therapy management (MTM) services by community pharmacists in the Western Region of Saudi Arabia. In addition, this study aims to measure patients' willingness to pay (WTP) for participating in the MTM program led by community pharmacists. Methods: Using a cross-sectional research design, a prevalidated questionnaire was developed and posted to respondents through either face-to-face interviews or online social media. All data were analyzed using SPSS, version 22.0, and all alpha values less than 0.05 were considered significant. Results: A total of 953 responses were obtained in this study. Overall, 47.6% of the respondents always buy their medications from different community pharmacies, and 46.1% of respondents said that community pharmacists always respond to all of their questions. In addition, 96% of respondents perceived the MTM program to be beneficial for patient care. Moreover, 70.3% of respondents were willing to register in the MTM program if implemented at community pharmacies. Conclusion: Residents in the Western Region of Saudi Arabia highly appreciate the additional values of the MTM program if implemented by community pharmacists. Decisions makers should encourage community pharmacists to plan for MTM services.